Evaluation of Deutetrabenazine's Potential to Delay Cardiac Repolarization Using Concentration‐QTc Analysis. Issue 1 (13th September 2022) - Schneider, Frank; Darpo, Borje; Loupe, Pippa S.; Xue, Hongqi; Knebel, Helena; Gutierrez, Maria; Gordon, Mark Forrest; Rabinovich‐Guilatt, Laura
Abstract: Deutetrabenazine (Austedo) is indicated in adults for chorea associated with Huntington disease and tardive dyskinesia. Escalating deutetrabenazine doses were administered to healthy volunteers who were cytochrome P450 2D6 extensive/intermediate metabolizers (EMs) or poor metabolizers (PMs) to determine pharmacokinetic exposure of parent drug and active metabolites (α‐dihydrotetrabenazine [α‐HTBZ] and β‐dihydrotetrabenazine [β‐HTBZ]), and collect corresponding electrocardiograms (ECGs) for evaluation of the cardiodynamic effect using concentration‐QTc (C‐QTc) modeling. Participants (12 EMs, 24 PMs) received placebo or single doses of deutetrabenazine (24, 48, and 72 mg) to achieve plasma concentrations exceeding therapeutic range in both cohorts. Pharmacokinetic samples were obtained over 72 hours after dosing and were time matched with 12‐lead ECGs extracted from continuous ECG recordings. C‐QTc analysis, using linear mixed‐effects modeling and model selection procedure, characterized the relationship between plasma concentrations of deutetrabenazine, deuterated α‐HTBZ and β‐HTBZ, and the change from baseline in QT interval corrected using Fridericia's formula. Deutetrabenazine exhibited linear kinetics, and a C‐QTc model with deuterated α‐HTBZ and β‐HTBZ was selected to best describe the C‐QTc relationship in pooled EM and PM data. This model predicted a placebo‐corrected Fridericia corrected QT interval prolongation higher than 10 milliseconds can be excluded at concentrations associated with the maximum recommended doses in both populations. Adverse events increased with higher exposure as reflected by the higher event number in the PM cohort receiving 48 and 72 mg doses. No subject discontinued due to cardiac‐related adverse events and no clinically relevant ECG findings were reported. Thus, this study found that deutetrabenazine does not have a clinically relevant effect on QT prolongation at maximum recommended doses in either cytochrome P450 2D6 EMs or PMs.